(untitled) (Journal of Atomic and Molecular Sciences, 2019)
The green fluorescent protein (GFP) has been widely used in biochemical and biological fields for its strong fluorescence emitting property. The effective fluorescence emitting property lies in its chromophore P-HBI. Compared with GFP, the low fluorescence quantum yield (0.2 vs. 0.8 of GFP) of the wild blue fluorescent protein (BFP) restrict its extensive applications. In order to enhance the fluorescent quantum yield of BFP, numerous attempts have been executed to modify the molecular configuration such as introducing the intramolecular hydrogen bond (IHB) or benzene ring to the parent structure. In the present work, we employed the high-level quantum chemistry calculation method CASSCF to investigate the excited state deactivation mechanism of 4-BFP, which is a newly synthesized BFP chromophore derivative by introducing a benzene ring to the five-membered heterocycle attempting to increase the fluorescence quantum yield. By combination of the optimization of stable electronic structures, scanning of potential energy surfaces and construction of energy profile, we found that the fluorescent quantum yield could not be enhanced for the 4-BFP molecule. One minimum energy conical intersection was located between the S1 and S0 states, which could act as the gateway for the 4-BFP to funnel to the ground state by the internal conversion process. The current work could provide fundamental guide for further molecular structure modification or improvement to enhance the fluorescent quantum yield of BFP analogues.